Peran Guru dalam Mengenalkan Pendidikan Seks sebagai Perlindungan Anak Usia Dini dari Pelecehan Seksual di Tk Aisyiyah Kota Bukittinggi - Mariyona, Kartika; Nugrahmi, Mega Ade; Rusdi, Pagdya Haninda Nusantri (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Early childhood's lack of understanding about sexual abuse means they don't want to talk and tell their parents when they experience abuse from other people, even those closest to them. Education about sex has a very good role, one of which is that it is useful as self-protection for children from the threat of sexual harassment. The function of this research is knowledge about sexual prevention which can reduce the incidence of sexual abuse in early childhood. Therefore, education regarding appropriate and good sexual prevention for early childhood is very important so that children have adequate provisions from an early age. The aim of this research is to determine the role of teachers as educators to provide education on the prevention of sexual harassment to young children at Aisyiyah Kindergarten. The method in this research is qualitative research, observation methods such as data collection, interviews and documentation. Data analysis by reducing data, presenting data and verifying data. The validity of the data was tested using triangulation techniques. This research obtained results where the role of teachers in introducing sex education to early childhood at Aisyiyah Kindergarten in sexual prevention was considered to be good, this can be known through teachers who act as teachers, educators and as facilitators for early childhood. The teacher displays the video Kuga I as the main asset for children in preventing sexual harassment, as well as facilitating education on preventing sexual harassment with pictures or posters to make it easier for children to remember.